Brusberg Berichte 20. - Galerie Brusberg, Hannover (Hannover : Galerie Brusberg, 1975)
Schultze, Bernard ; Wake, Richard ; Oppermann, Wolfgang ; Dörflinger, Hans ; Hausner, Rudolf ; Finsterlin, Hermann ; Kalish, Muriel
boek